How does increasing the minimum wage affect household food insecurity? - Nuworsu, Eugene K.; Katare, Bhagyashree (Journal of the Agricultural and Applied Economics Association, 2025)
Research suggests that higher minimum wages can act as an antipoverty tool, potentially resulting in improved welfare outcomes such as reducing food insecurity. This study examines the impact of state minimum wage increases on food insecurity from 2010 to 2019. Using household‐level data and quasi‐experimental approaches, we find evidence that suggests state minimum wage increases reduce the prevalence of very low food insecurity. Also, we find some limited evidence suggesting that minimum wage increases reduce the severity of food insecurity. Our results on the effects of minimum wage increases on very low food security for low‐income households hold across alternative methods.